Mobile Applications to Improve English Writing Skills Viewed from Critical Thinking Ability for Pre-Service Teachers - Haerazi, Haerazi; Utama, I Made Permadi; Hidayatullah, Heri (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This study was aimed at investigating; (1) the pre-service teachers used the MobApps (WhatsApp, U-Dictionary, and Email) to participate in mobile-assisted language learning (MALL) viewed from the critical thinking ability in the teaching of writing skills and; (2) the effectiveness of the Mobile-assisted language learning (MALL) towards pre-service teachers’ writing skills in relation to critical thinking ability. This study was a mixed method using the concurrent embedded strategy. The researchers involve qualitative strategies and quantitative strategies. Both kinds of data are collected simultaneously. This study was conducted in the English language education departments of FPBS IKIP Mataram, Indonesia. 58 pre-service teachers were involved in this study. The qualitative data were attained from pre-service teachers attending the writing classes using observation sheets. Meanwhile, the quantitative data were gained from experimental design through a nonequivalent control-group design. The groups were evaluated by using a writing test and a critical thinking test. The results showed that the pre-service teachers conducted a discussion of what they have to write. The learning activities are done under several stages. The end of this is that the pre-service teachers are able to create a complete descriptive text. Besides, the use of the MALL model was more effective than non-mobile learning to improve pre-service teachers’ writing skills viewed from critical thinking skills.